Sacred Skin: the Legend of St. Bartholomew in Spanish Art and Literature - Ferrera Lagoa, Alberto (Edad de Oro, 2021)
Reseña del libro Sacred Skin: the Legend of St. Bartholomew in Spanish Art and Literature, de Andrew M. Beresford (2020). Leiden: Brill, 352 pp. [ISBN: 978-90-04–40780-0].